2007 IEEE International Fuzzy Systems Conference 2007
DOI: 10.1109/fuzzy.2007.4295349
|View full text |Cite
|
Sign up to set email alerts
|

Chu Space and Approximable Concept Lattice in Fuzzy Setting

Abstract: In the paper, we introduce the notion of approximable concept in fuzzy setting, and show that approximable concept lattices represent algebraic completely lattice L-ordered sets in the sense of R. Belohlavek,.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In [4,5], we investigated the notion of approxmable concept in fuzzy setting. As a sequel, in the paper, we introduced the notions of directed set, way-below relation in fuzzy setting, and constructed the theory of continuous lattices of L-sets, and gave some examples, which incudes the algebra lattice of all L-approximable concepts, i.e., Example 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [4,5], we investigated the notion of approxmable concept in fuzzy setting. As a sequel, in the paper, we introduced the notions of directed set, way-below relation in fuzzy setting, and constructed the theory of continuous lattices of L-sets, and gave some examples, which incudes the algebra lattice of all L-approximable concepts, i.e., Example 5.…”
Section: Discussionmentioning
confidence: 99%
“…Example 5: In [4,5], we introduced the notion of approximable concept in fuzzy setting, and showed that the set of all approximable concepts (of attributes) forms an algebraic lattice of L-sets.…”
Section: Examplesmentioning
confidence: 99%
“…Relations between Chu spaces and category theory, linear logic, topology and other theories have been researched in e.g. [2], [6], [7], [9], [15], [16]. In this section, we will give basic definitions of Chu spaces.…”
Section: Chu Spacesmentioning
confidence: 99%
“…It should be noted that the notion of a framework is a special case of the notion of the formal context, due to B. Ganter and R. Wille [9], sometimes also referred as the Chu space [3]. Recall that a formal context is a triple (G, M, I), where G is a set of objects, M is a set of attributes and I ⊆ G×M is a binary relation.…”
Section: How To Topologize Everythingmentioning
confidence: 99%